Antioxidant and Chemoprevention Activity of Camelia Sinensis-Annona muricata Extract Combination against WiDr Cells Line - Nazariah Putri; Iwan Dewanto; Rifki Febriansah (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Antioxidant compounds have an essential role in inhibiting the process of cell proliferation and have a chemopreventive effect. This study aims to trace the presence of antioxidant compounds allegedly contained in tea leaves (Camelia Sinensis L.) and soursop leaves (Anonna muricata L.) and investigate their potency as chemopreventive agents. Research steps include (1) identify the active compounds using thin-layer chromatography (TLC); (2) find out the potential compounds against cancer cells by molecular docking using Autodock Vina; (3) conduct a potential antioxidant test using free radicals DPPH (1,1-diphenyl-2-pikrihidrazil); and (4) identify the cytotoxic effect on WiDr colon cancer cells test using MTT Assay method. The results showed that the ethanolic extract of Camellia sinensis-Annona muricata leaf combination was suspected of containing flavonoid compounds with Rf values of 0.66 and 0.68. Besides, the DPPH antioxidant test showed an IC50 value of 26.9 μg/mL. Cytotoxic potential against WiDr cells resulted in an IC50 value of 41 μg/mL. Furthermore, the molecular docking test of epigallocatechin gallate (EGCG) and Acetogenin compounds against bcl-xl target proteins showed the docking score of -8.1 kcal/mol and -6.7 kcal/mol, respectively. It concluded that the extract combination of Camelia Sinensis-Annona muricata leaf had strong potency as an antioxidant and chemopreventive agent against the WiDr colon cancer cells line.